PENGEMBANGAN PERANGKAT PEMBELAJARAN MATERI GERAK BERBASIS MASTERY LEARNING UNTUK SISWA SMA - Wahyuni, Sri; Sulhadi, Sulhadi (UPEJ Unnes Physics Education Journal, 2020)
This research aims to develop a motion?s learning material based on Mastery Learning for Senior High School?s students. The development of learning materials include Lesson Plans, learning media in the form of practicum videos, learning resources in the form of Mastery Learning?s Students Worksheet, and learning assessment instruments. The research method is Research and Development with 4-D development model that has been modified into 3-D. The 3-D research procedure includes: (1) defining, (2) designing, and (3) developing. The reserach was conducted at SMA N 14 Semarang Academic Year 2018/2019 with respondents 35 students. The results of the development of motion?s learning material based on Mastery Learning obtained results in the form of: validation of Lesson Plans feasibility is considered very feasible with a percentage of 92%; validation of practicum video feasibility by experts is considered very feasible with a percentage of 88.5%, teacher response to practicum videos is 82% with good categories; student responses to practicum videos amounted to 79% with good categories; validation of the feasibility of Mastery Learning?s Students Worksheet by experts of 86.5% with very good categories; the teacher's response to Mastery Learning?s Students Worksheet was 94% with a very good category, the readability level of Mastery Learning?s Students Worksheet was 94% and the validation of learning assessment instruments was 86% with a very feasible category.